El Excentrico, 1961-02-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 05, 1961 [5 de febrero de 1961]. Ano 11, No 8. Cover has headshots of seven people of the organizing committee of the 1961 Annual United Food Drive.